INTAKE OF MINANG CULTURAL VALUES AS STRENGTHENING THE CHARACTER OF THE NATION'S CHILDREN IN SHORT STORIES “TSUNAMI” BY ISMALINAR - Syahrul, Ninawati; Sunarti, Sastri; Atisah, Atisah; Fadlly, Harits (Prosiding Seminar Nasional dan Internasional HISKI, 2024)
This research will analyze the cultural values and local wisdom of the Minang ethnic group contained in the short story "Tsunami" by Ismalinar. This research uses an interpretive qualitative descriptive method with a literary anthropology approach. The focus of the analysis rests on local cultural values, both expressed and implied, by looking at the principle of benefit in the lives of Minang people and its impact as an enricher of national culture as a common property. The analysis data comes from literature studies, namely in the form of narrative text and dialogue between characters in the short story. The data analysis technique uses narrative analysis techniques. The findings from this research show that first, the language system in this short story contains several Minang vocabulary words that are synonymous with Indonesian; second, the knowledge system is knowledge of oneself, knowledge of people, knowledge of nature, and knowledge of God; third, the religious system is obedience in worship; fourth, the art system and livelihood system are not depicted in the short story; fifth, the technological system is the form of a gadang house; seventh, the social organization system is matrilineal and customary in consensus. All of this is certainly useful and can be a positive intake for students or the younger generation in strengthening the character of the nation's children.